(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2015)
Note: The authorship was changed on 23.02.2016 FROM Abdur Rakib, M. Kamruzzaman1*, Soyema Khatun1 and M. Moniruzzaman2 TO Abdur Rakib1*, M. Moniruzzaman2, M. Hasan3 and M.M. Rahman3. The authorship is changed due to request of the principal author to add two co-authors of his major professor and advisory committee member of postgraduate study and two co-authors are excluded from the authorship and acknowledged them for their contribution in the manuscript. ______________________________________________________________ Abstract: An experiment on coriander (Coriandrum sativum L.) was conducted at the experimental field of Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur during November 2012 to April 2013 to find out the suitable foliar doses and application frequency of urea and planofix (NAA). The experiment was laid out in factorial randomized complete block design with three replications. The treatment consisted of six foliar dozes viz. T1 (Tap water as control), T2 (0.10 % urea), T3 (0.25 % urea), T4 (0.40 % urea), T5 (5 ppm planofix) and T6 (10 ppm planofix) and three application frequencies viz. F1 [20 days after sowing (20 DAS)], F2 (30 DAS) and F3 (20 and 30 DAS). Maximum foliage yield (6.94 t/ha) was recorded in 10 ppm planofix coupled with its twice application at 20 and 30 DAS which was closely followed the foliage yield (6.33 t/ha) by 5 ppm planofix with the same application frequency. The foliage yield was increased with the increase in urea concentration. The highest foliage yield (5.37 t/ha) was also recorded from twice application of urea and planofix at 20 and 30 DAS, respectively. Planofix 10 ppm with its twice application at 20 and 30 DAS gave the highest benefit-cost of ration 2.51. Int. J. Agril. Res. Innov. & Tech. 5 (1): 40-44, June, 2015